2020
DOI: 10.20884/1.jks.2020.15.1.1069
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Assertive Training on Bullying in Junior High School

Abstract: <em>Bullying</em> merupakan fenomena yang umum dan masalah yang universal pada anak usia sekolah. <em>Bullying </em>dapat menimbulkan efek yang serius/ negatif terhadap kesehatan mental dan kesejahteraan anak. Salah satu strategi yang dapat dilakukan untuk mencegah bullying adalah dengan latihan ketrampilan asertif. Penelitian ini bertujuan untuk mengidentifikasi pengaruh latihan asertif terhadap pencegahan bullying pada siswa SMP 28 Padang. Desain penelitian adalah Quasi eksperimen den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…This self-protection activity must be owned by every teenager. Because the perpetrator of bullying will continue to carry out negative behavior toward the victim because the victim of bullying is weak (Herman et al, 2020). Therefore, a person's weaknesses must actually be improved into the potential that the individual has.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This self-protection activity must be owned by every teenager. Because the perpetrator of bullying will continue to carry out negative behavior toward the victim because the victim of bullying is weak (Herman et al, 2020). Therefore, a person's weaknesses must actually be improved into the potential that the individual has.…”
Section: Discussionmentioning
confidence: 99%
“…Bullying at school can happen to teenagers or teachers. They can be perpetrators or victims of bullying (Herman et al, 2020). Some boys and girls at school often fight, talk badly, spit carelessly, and bully their friends (Kurniyawan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by subsequent research which shows that being honest while paying attention to the conditions of other people can reduce bullying behavior in adolescents. 28,42,43 Assertive techniques are carried out with several contents, namely education, counseling, and games. Education about bullying and assertiveness is important to foster students' understanding and awareness regarding bullying and assertiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Assertiveness therapy is also carried out through theatrical dramas carried out by participants, so that participants can learn about assertive behavior that is carried out every day. 28 Assertiveness therapy is carried out to prevent and reduce bullying behavior in students at school. Participants are trained to be honest about their feelings.…”
Section: Games-based Assertive Therapymentioning
confidence: 99%
“…This can be achieved using group counseling services through behavioral counseling using assertive training techniques. This has been proven through several research results, including assertive exercises that can help students in understanding the concept of assertive behavior and how to apply it in daily life [4], then Hermalinda [5] found that assertive skill training could prevent teenagers from bullying behavior. Looking back at the results of existing research, among others, Karyanti [6] found that using ssertive training techniques were able to improve assertive behavior in victims of bullying.…”
Section: Introductionmentioning
confidence: 93%